2012
DOI: 10.1093/cercor/bhs185
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intra- and Inter-Regional Synchronization of Superior Temporal Cortex in Deaf People

Abstract: Functional organization of the brain can be fundamentally altered by auditory deprivation. Previous studies found that the superior temporal cortex in deaf people is reorganized to process non-auditory stimuli, as revealed by the extrinsic task-induced brain activities. However, it is unknown how the intrinsic activities of this region are impacted by deafness. This study explored this issue using resting-state functional magnetic resonance imaging. We examined 60 congenitally deaf (CD) individuals, 39 acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 81 publications
(104 reference statements)
4
40
3
Order By: Relevance
“…Such negative findings may be due to the fact that all UHL patients in current study were postlingual deaf. Previous study revealed that the age of the onset of deafness was critical to cortical plasticity [7,51]. Hence, we inferred that the plastic changes within auditory cortex of acquired UHL patients might be too mild to be significant statistically.…”
Section: Altered Whole-range Nfcs In Uhlmentioning
confidence: 80%
“…Such negative findings may be due to the fact that all UHL patients in current study were postlingual deaf. Previous study revealed that the age of the onset of deafness was critical to cortical plasticity [7,51]. Hence, we inferred that the plastic changes within auditory cortex of acquired UHL patients might be too mild to be significant statistically.…”
Section: Altered Whole-range Nfcs In Uhlmentioning
confidence: 80%
“…ReHo abnormalities may reflect abnormal local neuronal activity. A lower ReHo may represent local intraregional reduced neuron activity or regular disorder [ 7 ], which can strongly affect the brain neurons involved in information processing, as demonstrated in acquired deafness [ 10 ] and severe depression [ 11 ]. Enhanced ReHo reflects neuron activity in the region of the brain by increased time synchronization and strengthened brain function [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater language competence was associated with higher integration within nodes of the frontotemporal network. Better language function measured by story writing and a standardized test of Mandarin was associated with higher connectivity within the temporal nodes of the frontotemporal network (e.g., ReHo within right superior temporal gyrus [STG], and inter-and intrahemispheric connectivity of the right STG) in congenitally and acquired deaf individuals (Li et al, 2012b). Higher verbal IQ scores were associated with higher connectivity within the IFG in patients with epilepsy with left-sided, but not right-sided, seizure focus (Pravatà et al, 2011).…”
Section: Languagementioning
confidence: 99%